PABPN1L is required for maternal mRNA degradation after meiosis resumption - Chihiro EMORI; Mayo KODANI; Ferheen ABBASI; Masashi MORI; Masahito IKAWA (The Society for Reproduction and Development, 2023)
Poly(A)-binding proteins (PABPs) play roles in mRNA maturation, translational activity, and decay. The functions of PABPs, especially PABPN1 and PABPC1, in somatic cells have been well-studied. However, little is known about the roles of PABPs in oocytes because of the unique mechanisms of mRNA metabolism in oocytes. This study focused on PABPN1L and generated Pabpn1l knockout (KO) mice using the CRISPR/Cas9 system. After mating tests, we found that Pabpn1l KO females were infertile due to the failure of the embryos to develop to the 4-cell stage. RNA-seq analysis revealed aberrant mRNA persistence in Pabpn1l KO-MII oocytes, which indicates impaired mRNA degradation during the germinal vesicle (GV) to MII transition. We also revealed that the exogenous expression of Pabpn1l mRNA in KO-GV oocytes recovered defects of embryonic development. PABPN1L is partly indispensable for female fertility in mice, owing to its necessity for embryonic development, which is supported by mRNA degradation during GV to MII maturation.